2010
DOI: 10.5187/jast.2010.52.4.305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Level of CP and TDN in the Concentrate Supplement on Growth Performances and Carcass Characteristics in Hanwoo Steers during Final Fattening Period

Abstract: Seventy two Hanwoo steers in final fattening period (585.87±41.02kg) were randomly assigned to 3 groups, LPLT (relatively low protein and low energy; CP 12%, TDN 73%), LPHT (relatively low protein and high energy; CP 12%, TDN 75%) and HPHT (relatively high protein and high energy; CP 14%, TDN 75%) in concentrate feed for 163 days in order to investigate the effects on growth performance, carcass characteristics, and longissimus dorsi muscle's chemical compositions. Rice straw was also fed as a roughage. Becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…These results probably occurred because pTMR and cTMR had higher TDN than nTMR. Similarly, Jeong et al (2010) found that feed with high TDN (75% TDN) increased the rib eye area in Hanwoo steers. On the other hand, nTMR provided a significantly higher omasum weight compared with pTMR and cTMR, which caused from the high amount of CF in the intake.…”
Section: Discussionmentioning
confidence: 75%
“…These results probably occurred because pTMR and cTMR had higher TDN than nTMR. Similarly, Jeong et al (2010) found that feed with high TDN (75% TDN) increased the rib eye area in Hanwoo steers. On the other hand, nTMR provided a significantly higher omasum weight compared with pTMR and cTMR, which caused from the high amount of CF in the intake.…”
Section: Discussionmentioning
confidence: 75%
“…ble-muscled crossbred young bulls. Conversely, Jeong et al [15] studied the responses to low-(12%) and high-CP (14%) diets with a similar total digestible nutrient (TDN) content (75%) in the finishing Hanwoo steers, and found that the high-CP diet increased final BW and feed conversion ratio while slightly affecting DMI. 6) 3.0 3.0 3.0 --Texture score 7) 1.…”
Section: Discussion Productivitymentioning
confidence: 99%
“…Likewise, Dal Maso et al [ 14 ] reported that growth performance was negligibly affected when dietary CP concentrations decreased from 14.7% to 11.0% in double-muscled crossbred young bulls. Conversely, Jeong et al [ 15 ] studied the responses to low- (12%) and high-CP (14%) diets with a similar total digestible nutrient (TDN) content (75%) in the finishing Hanwoo steers, and found that the high-CP diet increased final BW and feed conversion ratio while slightly affecting DMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy level of feed is known to be a major factor affecting the growth performance, carcass characteristics, and fat deposition in beef cattle (Chung et al, 2015), with total digestible nutrients (TDN) being the most widely used energy estimation unit. In particular, TDN levels of late fattening concentrates affect average daily gain (ADG) and intramuscular fat deposition of fattening cattle (Jeong et al, 2010). Therefore, it is an important factor for producing high quality meat from Hanwoo steers (Lee, 2017).…”
Section: Introductionmentioning
confidence: 99%